Anthropogenic Impacts on Atmospheric Carbonyl Sulfide Since the 19th Century Inferred From Polar Firn Air and Ice Core Measurements. Issue 16 (19th August 2020) - Aydin, M.; Britten, G. L.; Montzka, S. A.; Buizert, C.; Primeau, F.; Petrenko, V.; Battle, M. B.; Nicewonger, M. R.; Patterson, J.; Hmiel, B.; Saltzman, E. S.
Abstract: Carbonyl sulfide (COS) was measured in firn air collected during seven different field campaigns carried out at four different sites in Greenland and Antarctica between 2001 and 2015. A Bayesian probabilistic statistical model is used to conduct multisite inversions and to reconstruct separate atmospheric histories for Greenland and Antarctica. The firn air inversions cover most of the 20th century over Greenland and extend back to the 19th century over Antarctica. The derived atmospheric histories are consistent with independent surface air time series data from the corresponding sites and the Antarctic ice core COS records during periods of overlap. Atmospheric COS levels began to increase over preindustrial levels starting in the 19th century, and the increase continued for much of the 20th century. Atmospheric COS peaked at higher than present‐day levels around 1975 CE over Greenland and around 1987 CE over Antarctica. An atmosphere/surface ocean box model is used to investigate the possible causes of observed variability. The results suggest that changes in the magnitude and location of anthropogenic sources have had a strong influence on the observed atmospheric COS variability. Plain Language Summary: Carbonyl sulfide (COS) is the most abundant sulfur containing trace gas in the atmosphere. We measured COS in firn air collected during several different field campaigns carried out at Greenland and Antarctic ice sheets. Firn air is the unincorporated old air found between the surface snow and the underlying ice that can be used to determine past changes in atmospheric composition. Firn air COS measurements were used to determine atmospheric COS variability since the 19th century. In our analysis, we also make use of measurements of COS in ice core air that provide information atmospheric COS levels during the 17th and 18th centuries. The results demonstrate that atmospheric COS increased from a stable preindustrial background level starting in the 19th century and peaked around 1975 CE over Greenland and around 1987 CE over Antarctica. The increase is on the order of 60% and is primarily driven by emissions linked various human activities. Key Points: We conducted a simultaneous multisite inversion of firn air COS data from Greenland and Antarctic ice sheets for the first time Analysis provides hemispheric records of atmospheric COS that display large increases through the first 70–80 years of the 20th century Model results suggest anthropogenic emissions are the primary driver of decadal changes in atmospheric COS levels during the study period